Bromelain Loading and Release from a Hydrogel Formulated Using Alginate and Arabic Gum - Ataide, Janaína Artem; Cefali, Letícia Caramori; Rebelo, Marcia de Araujo; Spir, Lívia Genovez; Tambourgi, Elias Basile; Jozala, Angela Faustino; Chaud, Marco Vinícius; Silveira, Edgar; Gu, Xiaochen; Gava Mazzola, Priscila (Planta Medica, 2017)
An ideal wound dressing ensures a moist environment around the wound area and absorbs exudates from the wound surface. Topical application of bromelain to incised wounds has been shown to reprogram the wound microenvironment to promote effective tissue repair. Combining the characteristics of hydrogels and bromelain is therefore of great interest. Herein, we describe the development of a hydrogel, formulated using alginate and Arabic gum, for bromelain loading and release. The hydrogel formulation was evaluated using response surface methodology, considering the pH value and the concentration of alginate and Arabic gum. Bromelain loading and release were evaluated based on passive diffusion. Differential scanning calorimetry and Fourier transform infrared spectroscopy were performed to confirm bromelain immobilization in the hydrogel. The final hydrogel formulation had a swelling ratio of 227 % and incorporated 19 % of bromelain from a bromelain solution. Bromelain immobilization in the hydrogel was the result of hydrogen bond formation and was optimal at 4 °C after 4 h of contact. This evidence suggests that bromelain entrapment into a hydrogel is a promising strategy for the development of wound dressings that support the debridement of burns and wounds.
Keywords: bromelain; hydrogel; alginate; Arabic gum; formulation development; Ananas comosus L.; Bromeliaceae